Modeling crowdfunders’ behavioral intention to adopt the crowdfunding-waqf model (CWM) in Malaysia: the theory of the technology acceptance model - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Allah Pitchay, Anwar (Emerald Publishing Limited, 2018)
Purpose – Waqf institutions in many Muslim countries including in Malaysia are facing liquidity constraints in developing waqf land. This paper aims to offer a sustainable model of source of financing for waqf institutions to meet their liquidity constraint in developing waqf land, which is known as the crowdfunding–waqf model (CWM). Later, CWM validated its acceptance in the field among the crowdfunders by adopting the theory of technology acceptance model (TAM). Design/methodology/approach – The primary data are collected from the survey administered to donors or crowdfunders in Selangor, Penang, Johor and Pahang. The total number of respondents are n = 1,000. The analysis is conducted using structural equation modeling (SEM). Findings – Based on findings, both the perceived usefulness and perceived easy to use of CWMare found to have a positive impact on the behavioral intention of crowdfunders or donors in assisting waqf institutions to develop waqf land in Malaysia. Furthermore, perceived easy to use has a positive relationship and direct effect on perceived usefulness of crowdfunders to use the CWM. Research limitations/implications – There are some limitations of the current study. The sample size and area of study become the obvious limitations. Thus, there is a need for caution in theinterpretation of the results, and the conclusion cannot be as generalized. Besides, the use of current factors might limit the ability to explore other potentially important determinants of the crowdfunders’ behavioral intention on using CWM. Thus, future research can be conducted by incorporating new factors and provide new insights for optimizing CWM. Other potential moderator variables should be included into the research model in order to obtain more robust results. Practical implications – The findings of this paper will provide a new avenue for waqf institutions to raise funds for developing waqf land, particularly in Malaysia. The present study also has implications for the government and policymakers. Through CWM, it enables to reduce the expenses of the government for the development of waqf land. Indeed, CWM could be applied in other Muslim countries that are facing liquidity constraint in developing waqf land.